The Application of Immersive Interactive Technology in Animation Teaching. (6th October 2022) - Sun, Zhiying; Liu, Jing
Abstract : In order to improve the interactive and immersive effect of animation teaching, this paper applies immersive interactive technology to animation teaching. In the light processing of animation teaching, this paper uses four-step phase shift and PCA algorithm to process the interference fringes with vibration effects collected by the CCD camera. The influence of white light background noise in the environment on the laser speckle measurement can be effectively filtered by adding a filter device to the imaging optical path. In order to explore the antivibration ability of different phase extraction algorithms of laser speckle interferometry in the presence of vibration in the measurement environment, this paper constructs an application model of immersive interactive technology in animation teaching. From the test results, it can be seen that the application effect of the immersive interactive technology proposed in this paper in animation teaching is relatively obvious.